Pengaruh Partisipasi Anggaran terhadap Senjangan Anggaran dengan Informasi Asimetri, Budaya Organisasi, Komitmen Organisasi,dan Ketidakpastian Lingkungan Sebagai Variabel Moderating (Studi Empiris Pada SKPD Kab. Pelalawan) - Sundari Setia Wardani; Vince Ratnawati; Rusli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of the research was examined the effect of budgetary participation on budgetary slack using information asymetry, organizational culture, organizational commitment, and environmental uncertainty as moderating variabels. Population is the Regional Working Units (SKPD) in Pelalawan. Data collected by distributing questionnaires to the respondents.This research use multiple regression analysis model by (Statistical Product Service Solution) version 17.0. The results show that the first hypothesis budgetary participation and significant positive impact on budgetary slack. Furthermore, the second hypothesis, three and four information asymmetry, organizational culture, organizational commitment and the moderating effect significant relationship with the budgetary participation budgetary slack. The fifth hypothesis failed environmental uncertainty moderate the relationship between budgetary participation and budgetary slack. Keyword :budgetary Participation, information asymetry, organizational culture, organizational commitment, environmental uncertainty, budgetary slack.